Effect of process and formulation variables on the preparation of parenteral paclitaxel-loaded biodegradable polymeric nanoparticles: A co-surfactant study - Navneet Sharma; Parshotam Madan; Senshang Lin (Elsevier, 2016)
The purpose of this study was to evaluate the effect of process (homogenization speed and evaporation time) and formulation (aqueous/organic phase ratio, surfactant concentration, polymer type and concentration, and drug amount) variables on the preparation of paclitaxel-loaded biodegradable polymeric nanoparticles using modified solvent evaporation technique. Thereafter, a formulation was selected and subjected to evaluation of inclusion of a co-surfactant for further reduction of particle size. Particle size, encapsulation efficiency and in-vitro drug release kinetics were evaluated. It was observed that the inclusion of vitamin E TPGS (0.01%), Poloxamer 188 (0.5%) or Tween 80 (0.25%) reduced the particle size of nanoparticles to 230, 244 or 301 nm from 438 nm, respectively. Encapsulation efficiency increased for both vitamin E TPGS and Poloxamer 188 up to concentration at 0.010% and 0.25%, respectively, while this was not the case for Tween 80. Comparison of drug release kinetics demonstrated that drug release accelerated from paclitaxel-loaded biodegradable nanoparticles prepared with the inclusion of Tween 80 but was delayed for Poloxamer 188 and vitamin E TPGS. Thus, it was concluded that the particle size of the nanoparticles could be reduced further and the paclitaxel release kinetics could easily be adjusted by taking advantage by the inclusion of a co-surfactant.